Influence of genital herpes on results of fluorescent treponemal antibody absorption test. Issue 5 (October 1978) - Chapel, T; Jeffries, C D; Brown, W J; Stewart, J A
Abstract : Both the fluorescent treponemal antibody absorption (FTS-ABS) test and Venereal Disease Laboratory (VDRL) test for syphilis were performed routinely on 113 men with histories of genital ulcerations. The difference in negative VDRL and borderline FTS-ABS results between patients with and without herpes simplex virus in their genital ulcers and no evidence of previous or untreated syphilis was not statistically significant. Furthermore, use of the FTA-ABS test as a confirmatory rather than a screening test eliminates false-positive, borderline, or reactive results in patients with non-syphilitic ulcers.